An Intraductal Variant of Acinar Cell Carcinoma. Report of a Case - Moletta, Lucia; Milanetto, Anna Caterina; Alaggio, Rita; Sperti, Cosimo; Pedrazzoli, Sergio; Pasquali, Claudio (JOP. Journal of the Pancreas, 2012)
Context Pancreatic intraductal neoplasms in the past few years had increasing importance, as the incidence of these tumors (especially intraductal papillary mucinous neoplasms-IPMNs) has grown and their significance as precursors of invasive cancer is now better appreciated. Acinar cell carcinomas (ACCs) are typically solid tumors; however, a few cases of ACCs with intraductal growth pattern have been described in the literature. These kind of neoplasia can be easily mistaken for IPMNs. We report a case of an acinar cell carcinoma of the pancreatic head with a polipoid intraductal growth. Case report A 42-year-old woman was observed in our unit for recurrent epigastric pain. Blood exams showed a mild increase of serum lipase and amylase levels (141 and 116 U/L, respectively). Serum tumor markers were negative. An abdominal ultrasound showed an hypoechoic area in the pancreatic head, with a maximum diameter of 14.5 mm. The patient underwent also a CT scan which confirmed the pancreatic head mass and showed a dilated Wirsung duct. A 18F-fluorodeoxyglucose positron emission tomography showed a pathological uptake of the tracer in an area of 2 cm, corresponding to the pancreatic head, with a maximum SUV of 7.5. In the suspicion of a degenerated IPMN, the patient underwent a pancreaticoduodenectomy. The post-operative course was uneventful. Histology showed an acinar cell carcinoma of the pancreatic head with a polypoid intraductal growth (T2 N0 M0). The tumor size was 2.0x2.5 cm, the mitotic index was 30x10 HPF. Immunohistochemistry studies found trypsin expression and no mucin was detected. Surgical margins were free. The patient underwent six course gemcitabine chemotherapy and is still alive 62 months after surgery without evidence of recurrence. Conclusion A few cases of ACCs with intraductal growth pattern have been described in the literature. The clinical significance of this variant is difficult to determine; however, it appears that metastasis at presentation is less common than typically seen in ACCs.